Overcoming Recruitment Challenges for Securing a Survey Sample of Caregivers of Community-Dwelling Older Adults with Multiple Chronic Conditions - Allison Williams; Wendy Duggleby; Jenny Ploeg; Maureen Markle-Reid; Heather Moquin; Jilan Yang (Journal of Human Health Research, 2017)
This paper discusses the challenges in recruiting a diverse sample of caregivers of older adults with multiple chronic conditions in two Canadian provinces – Ontario and Alberta, as well as the successful strategies to overcome these challenges. Four strategies were employed to overcome the recruitment challenges experienced. These included: (1) using a multi-pronged recruitment strategy with persistence; (2) knowing the location of the sample in the community; (3) weekly reporting by team members primarily responsible for recruitment and data collection, and; (4) regular team meetings to build on successful recruitment strategies while troubleshooting new approaches. These four strategies complemented one another. The most effective strategies in Alberta (recruiting over 50% of participants) were newspaper advertisements and working with the Alberta Caregivers Association and the Alzheimer Society of Alberta/NWT. In Ontario, the most effective strategy was door to door flyers (recruiting 61.5% of participants).
Keywords: sample recruitment